2023
DOI: 10.1097/moh.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Modelling arterial thrombus formation in vitro

Amelia Drysdale,
Azziza Zaabalawi,
Sarah Jones

Abstract: Purpose of review Models of arterial thrombus formation represent a vital experimental tool to investigate platelet function and test novel antithrombotic drugs. This review highlights some of the recent advances in modelling thrombus formation in vitro and suggests potential future directions. Recent findings Microfluidic devices and the availability of commercial chips in addition to enhanced accessibility of 3D printing has facilitated a rapid surge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Results indicating that platelet responses are altered when collagens are exposed in the presence of vascular proteoglycans, such as those found in both plaque rupture and plaque erosion, may have implications on antiplatelet efficacy, which is routinely investigated in vitro using type I collagen in isolation [28][29][30][31][32]. The differences observed between 'rupture' and 'erosion' matrices also indicated that different mechanisms may be involved in the formation of arterial thrombi; therefore, the efficacy of antithrombotic drugs may differ depending on plaque type.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicating that platelet responses are altered when collagens are exposed in the presence of vascular proteoglycans, such as those found in both plaque rupture and plaque erosion, may have implications on antiplatelet efficacy, which is routinely investigated in vitro using type I collagen in isolation [28][29][30][31][32]. The differences observed between 'rupture' and 'erosion' matrices also indicated that different mechanisms may be involved in the formation of arterial thrombi; therefore, the efficacy of antithrombotic drugs may differ depending on plaque type.…”
Section: Discussionmentioning
confidence: 99%